Oikopolitics, regulation and privacy: an essay on the governmental nature of the right to private life - Nasir, Muhammad Ali (Philosophy & social criticism, 2019)
This essay focuses on the interrelationship of regulation and private life in human rights. It argues three main points. (1) Article 8 connects the question of protection of private lives and privacies with the question of their management. Thus, Article 8 orients regulatory practices to private lives and privacies. (2) Article 8’s holders are autonomous to the extent that laws respect their private lives and privacies. They are not autonomous in a ‘pre-political’ sense, where we might expect legal rules to protect an already autonomous private life or privacy. (3) Article 8 does not simply prohibit or permit acts. In certain cases, it also ‘enables’ acts. Then, this essay introduces the idea of oikopolitics. This idea allows us to capture these three points in a useful manner. By this idea, this essay means the context (a) where the interpretation of privacy reaches out to broader social practices and norms and (b) where the status of rights-holders living their private lives makes them objects of attention.